2009
DOI: 10.1002/asi.21230
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors influencing application of ICT by agricultural graduate students

Abstract: With improving technology in the world, particularly Information and Communication Technology (ICT), people need to make an effort to keep up with the new technology. The importance of ICT in higher education continues to grow year by year.The purpose of this study was to analyze factors influencing application of ICT by agricultural graduate students. The statistical population included agricultural graduate students in colleges of agriculture at the University of Tehran. A sample of 110 students was selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…(Verhoeven et al 2010; see also Pouratashi and Rezvanfar 2010;Fillion et al 2009). The nucleus of TAM was preserved, but expanded with some other variables (e.g.…”
Section: Theoretical Backgroundmentioning
confidence: 92%
“…(Verhoeven et al 2010; see also Pouratashi and Rezvanfar 2010;Fillion et al 2009). The nucleus of TAM was preserved, but expanded with some other variables (e.g.…”
Section: Theoretical Backgroundmentioning
confidence: 92%
“…While there is a large body of literature about the factors that influence teachers' adoption and use of ICT in their teaching, little literature about learners' experiences exists. Skills, support, and facilities are factors that influence students (Pouratashi & Rezvanfar, 2010). However, Pouratashi and Rezvanfar conclude that support and facilities impose indirect effects while skills have both direct and indirect effects; "given the direct effect on application of ICT, we infer that when students' skills improve, they are more likely to use ICT" (Pouratashi & Rezvanfar, 2010, p. 81).…”
Section: The Student Perspectivementioning
confidence: 99%
“…English language competency is significantly associated with the use of IT (17,40,41). This finding could be explained by many resources in English available in international databases.…”
Section: Discussionmentioning
confidence: 99%
“…The familiarity rate of the students with Internet and Worldwide Web was reported to be 39%. Pouratashi and Rezvanfar (17) revealed that mastery over, support for, and ease of IT use were three important factors for students' use of IT. The mastery over IT use was the most important factor.…”
Section: Introductionmentioning
confidence: 99%